Perceptions of unilluminated occupations a survey of Danish occupational therapists - Nina Mønsted; Lisa Mahaffey; Christina Jessen Winge; Anette Enemark Larsen (Scandinavian Journal of Occupational Therapy)
Background In occupational therapy and -science positive aspects of occupation are highlighted. Recently, this discourse has been questioned, as it might leave out occupations – referred to as unilluminated occupations (UO) – that hold value to people, without fitting the positive ideal.Aim To translate UO into Danish and to examine how occupational therapists (OTs) view and address UO.Methods A survey developed in USA was translated into Danish and distributed to OTs across Denmark. We added questions on the Danish wording of the concepts, including a content validity index (CVI). Data was subjected to a descriptive analysis.Results The respondents agreed that OTs must include examining the purpose and meaning of UO, however without having a responsibility to support performing these UO. The applied translation: high risk (risikable), unhealthy (usunde), unethical (uetiske), immoral (umoralske), and unacceptable (uacceptable) were deemed relevant in Danish, established by CVIs on 0.72–0.90.Conclusions and significance Although most respondents were positive towards examining and acknowledging clients’ purpose and meaning of UO, no clear consensus when addressing UO in interventions was seen. Further research might shed light on ways to approach UO both in assessment and intervention. The Danish terms appeared relevant to encompass UO.